Overexpression of tau results in defective synaptic transmission in Drosophila neuromuscular junctions. (20th January 2006) - Chee, F.; Mudher, A.; Newman, T.A.; Cuttle, M.; Lovestone, S.; Shepherd, D.
Abstract : Synaptic dysfunction is believed to be an early pathological change in neurodegenerative diseases and may cause the earliest clinical symptoms. We have used Drosophila to model a tauopathy in order to analyse the earliest neuronal and synaptic dysfunction. Our work has shown that overexpression of human tau (0N3R) in larval motor neurons causes a disruption of axonal transport and a morphological and functional disruption of NMJs (neuromuscular junctions). Tau-expressing NMJs are smaller with an abnormal structure. Despite abnormal morphology, tau-expressing NMJs retain synaptotagmin expression and can form active zones. Tau-expressing NMJs are functionally abnormal and exhibit disrupted vesicle cycling and synaptic transmission. At low-frequency stimulation (1 Hz), ESPs (evoked synaptic potentials) produced by tau-expressing motor neurons were indistinguishable from wild-type; however, following high-frequency stimulation (50 Hz), ESPs from tau-expressing NMJs were significantly decreased in amplitude. To investigate the mechanism underlying the change in ESPs, we analysed the relative numbers and distribution of mitochondria. This revealed that motor neurons expressing tau had a significant reduction in the number of detectable mitochondria in the pre-synaptic terminal. Our results demonstrate that tau overexpression results in synaptic dysfunction, associated with a reduced complement of functional mitochondria. These findings suggest that disruption of axonal transport and synaptic transmission may be key components of the pathogenic mechanism that underlie neuronal dysfunction in the early stages of tauopathies.